IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN AL-QUR’AN HADIS DENGAN METODE BERNYANYI DI MADRASAH IBTIDAIYAH - Mursal Aziz; Hairullah; Desy Rahma Wati (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2024)
Singing is a learning method that uses sung poetry in an effort to make it easier to convey material in the learning process. This research aims to describe the implementation of the independent curriculum in Al-Qur'an Hadith subjects using the singing method at Madrasah Ibtidaiyah. This research method uses qualitative research methods carried out at Madrasah Ibtidaiyah. The results of this research are that the implementation of the independent curriculum through the singing method in the Al-Qur'an Hadith subject at Madrasah Ibtidaiyah has three stages, namely planning at the beginning of learning with the teacher making teaching modules, determining the tune of the song, making lyrics or poems that are adapted to the Al-Quran lesson material. Al-Qu'ran Hadith, namely about Surah Al-'Alaq, compiling the words to make a song, then the songs sung are songs about the learning material and the verses read must be in accordance with the makhraj. Next, the implementation stage begins with opening activities, core activities and closing activities. The implementation of the independent curriculum on Al-Qur'an Hadith subjects using the singing method at Madrasah Ibtidaiyah makes class conditions enjoyable, students look active during teaching and learning activities, makes it easier for students to remember the material that has been taught, learning becomes effective, students feel happy, easy to remember without coercion, not boring, so it attracts students' interest in learning and makes the class atmosphere happy in participating in the learning process and they prefer to use the singing method rather than other methods.